2021
DOI: 10.1088/1755-1315/682/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Bearing Capacity of Marine Clay using Polyurethane Columns

Abstract: Problematic soil such as marine clay causes structures or pavement to crack and collapse as marine clay possesses low bearing capacity. Therefore, ground improvement is usually conducted to improve the bearing capacity. Since the use of cement for strengthening weak soil is not environmental-friendly, the aim of this study is to improve the bearing capacity of marine clay using polyurethane (PU) columns. The properties of the marine clay collected from Batu Pahat determined were particle size distribution, Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Bearing capacity is the ability of the soil to support the weight of structures and vehicles safely and without shear failure in the event of deformation or severe settlement. If the natural soil has low bearing capacity and shear strength, it may not be able to support the loads of pavements or roads (Azhar et al, 2017;Che Mamat et al, 2019;Harianto et al, 2022;Hasyimi & Syahril, 2021;Prajudi & Syahril, 2021;Yong et al, 2021). An example of the situation of a soil with low bearing capacity and low shear strength is shown in Figure 2.…”
Section: Low Bearing Capacity and Shearmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing capacity is the ability of the soil to support the weight of structures and vehicles safely and without shear failure in the event of deformation or severe settlement. If the natural soil has low bearing capacity and shear strength, it may not be able to support the loads of pavements or roads (Azhar et al, 2017;Che Mamat et al, 2019;Harianto et al, 2022;Hasyimi & Syahril, 2021;Prajudi & Syahril, 2021;Yong et al, 2021). An example of the situation of a soil with low bearing capacity and low shear strength is shown in Figure 2.…”
Section: Low Bearing Capacity and Shearmentioning
confidence: 99%
“…Furthermore, it is now reported that approximately 2-8% of global electricity consumption is attributed to the cement manufacturing process (Kim et al, 2018;N. Mohamad et al, 2021;Nilimaa, 2023;Yong et al, 2021). Therefore, there is a need to look for an alternative soil stabiliser such as fibre.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane columns can be used to increase the bearing capacity of marine clay, according to Yong et al [19]. The results demonstrated that as the PU columns' length increased, increasing the marine clay's ultimate bearing capacity.…”
Section: Introductionmentioning
confidence: 99%